Gripping devices of industrial robots for manipulating offset dish antenna billets and controlling their shape - Savkiv, Volodymyr; Mykhailyshyn, Roman; Maruschak, Pavlo; Kyrylovych, Valerii; Duchon, Frantisek; Chovanec, Ľuboš (Transport, 2021)
Invention proposes an adaptive gripping device of an industrial robot, which combines functions of capturing different-shape manipulation objects with control of deviations from the shape of these objects. The device is a T-shaped frame with three Bernoulli grips pivotally mounted thereon and a pneumatic sensor. Analytical dependencies are presented for determination of design parameters of adaptive gripping device and calculation of required lifting force of each of Bernoulli Gripping Device (BGD). Formula is derived for determining its position of pneumatic sensor on frame of gripping devices. In the ANSYS-CFX software environment, numerical simulation of airflow dynamics in the gap between the cooperating BGD surfaces and the offset mirror antenna plate blank. The simulation was based on the Reynolds-Averaged Navier–Stokes (RANS) equations of viscous gas dynamics, the Shear Stress Transport (SST) model of turbulence, and the y model of laminar–turbulent transition. As a result of the simulation, the effect of the curvature radius of the surface of the plates of offset mirror antennas on the BGD power characteristics was determined.